Development of a non-radioactive molecular hybridization probe for detecting Strawberry mottle virus in strawberry - Asinari, Florencia (2016)
The vegetative propagation of strawberries favors transmission of systemic pathogens, such as viruses, which are one of the main yield-limiting factors for this crop. More than 20 viruses have been described as infecting this species; one of the most frequent is the Strawberry mottle virus (SMoV), which is responsible for significant economic losses. SMoV is usually detected by reverse transcription polymerase chain reaction (RT-PCR), given that serum is not available for serological tests. In this study, a non-radioactive molecular probe was developed for SMoV detection. The cDNA was synthesized by RT-PCR using specific primers designed from the 3’UTR region of the viral genome. The cloned cDNA segment was labeled and used as a probe. Six RNA extraction protocols were evaluated, and the modified cetyltrimethylammonium bromide (CTAB) method showed the highest sensitivity level. Leaves at different phenological stages and petioles were evaluated; the highest reaction was observed in old leaves and in petioles